National Consensus on Management of Dyspepsia and Helicobacter pylori Infection - Ari F Syam; Marcellus Simadibrata; Dadang Makmun; Murdani Abdullah; Achmad Fauzi; Kaka Renaldi; Hasan Maulahela; Amanda P Utari (Acta Medica Indonesiana, 2017)
Dyspepsia is one of numerous general complaints, which is commonly encountered by doctors of various disciplines. In daily practice, the complaint is not only limited for gastroenterologists. Knowledge on pathophysiology of dyspepsia have been developing continuously since a scientific investigation has been started in 1980’s, which considers Helicobacter pylori as one of key factor in managing dyspepsia, either it is associated with ulcer or non-ulcer. The management of dyspepsia cannot be separated from the management of H. pylori and there is an additional new knowledge associated with definition, pathophysiology, diagnosis and treatment of both dyspepsia and H. pylori infection. This consensus document on the management of dyspepsia and H. pylori infection in Indonesia has been developed using the evidence-based medicine principles; therefore, it can be used as a reference for doctors in dealing with dyspepsia and H. pylori infection cases in their daily practice. It is expected that with the new consensus, doctors can provide greater service to their patients who have dyspepsia and H. pylori infection.